Software engineering : - Vliet, Hans van (John Wiley & Sons, 2008)
Integral to this author's approach to the subject is the focus on managerial aspects and human factors involved in software projects. To reflect the changes taking place within software engineering, the new edition includes a major update on architecture, sections on the new developments such as UML2 and commercial off-the-shelf (COTS) products.